2002
DOI: 10.2140/pjm.2002.203.461
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic behaviour at infinity of three-dimensional steady viscoelastic flows

Abstract: The steady motion of viscoelastic fluids is investigated in a three-dimensional exterior domain. Results concerning existence, uniqueness and asymptotic behaviour are obtained using appropriately constructed function spaces in which the elements are defined as a sum of the main asymptotic term and of the remainder living in a proper weighted Sobolev space. The equations are written as a coupled system that, at the first stage, can be studied as two linear problems composed of a Stokes system and a transport eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…where Q 1 = (0, ∞)×S 1 , cf. [10]. Hence, if y ∈ V l (B R 0 ) and z ∈ V l (B R 0 ) and l 2, standard embeddings imply that e ( + −2l+3)t y(e t , , )z(e t , , ) ∈ H l (Q 1 )…”
Section: Artificial Boundary Conditions For Viscoelastic Flowsmentioning
confidence: 98%
See 3 more Smart Citations
“…where Q 1 = (0, ∞)×S 1 , cf. [10]. Hence, if y ∈ V l (B R 0 ) and z ∈ V l (B R 0 ) and l 2, standard embeddings imply that e ( + −2l+3)t y(e t , , )z(e t , , ) ∈ H l (Q 1 )…”
Section: Artificial Boundary Conditions For Viscoelastic Flowsmentioning
confidence: 98%
“…It must be stressed, however, that this is the only information available for the main asymptotic term.In principle, a similar idea could work for non-Newtonian flows. As for the asymptotic behaviour, the exterior problem for an Oldroyd-B fluid has already been studied in weighted spaces in [10].There it was shown that, although the Navier-Stokes equations are perturbed by the divergence of the extra-stress tensor, they maintain the (Navier-Stokes) asymptotic form. Hence, the ABCs for the Navier-Stokes part in the equations need only to be complemented with an additional term.The solution of the transport equation does not need to satisfy any boundary conditions and, therefore, at the first sight the ABCs stemming from the Navier-Stokes part seem to be enough for the approximation problem in R .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome this difficulty, we employ the technique of weighted spaces with detached asymptotics invented in [26] and further developed in [28,41,31,33,34,30]. Let us fix …”
Section: Is Continuous If and Only Ifmentioning
confidence: 99%